Effect of carbonic anhydrase enzymes on strength of soil cement - Kingnoi, Namthip; Ayawanna, Jiratchaya; Mase, Lindung Zalbuin; Omar, Rohayu Che; Chaiyaput, Salisa (My University, 2026)
This research proposes the originality of using carbonic anhydrase (CA) biocatalyst enzyme with soil cement material for strength development. The soft Bangkok clay with cement up to 30 wt% of dried soil was prepared with the addition of CA at an amount of 100 µl and a concentration of 100 µM. The suitable preparation and curing method of soil cement containing CA was also investigated using different mixing methods (dry mixing and wet mixing) and curing conditions (air curing and plastic wrap curing) for up to 28 days. The improvement of soil cement strength was achieved by increasing cement content and curing time. The compressive strength of soil cement is highly improved with the addition of CA, particularly in the air-curing condition. The formation of CaCO3 was observed with a tightened microstructure. In addition, the wet mixing method is favorable for improving strength with biocatalyst enzymes due to the dispersion of hydrated cement particles. Mixing small amounts of CA in soil cement not only enhances strength but also contributes to environmental sustainability, making it a viable option for sustainable future construction applications and adaptable ground improvement techniques.
Keywords: Biocatalyst; Curing; Improve strength; Mixing; Soft Bangkok clay; Soft clay